Ten new species of Rhagovelia in the angustipes complex (Hemiptera: Heteroptera: Veliidae) from Colombia, with a key to the Colombian species - Padilla-Gil, Dora Nancy (Zootaxa, 2015)
Ten new species of Rhagovelia are described from Colombia as follows: Rhagovelia penta sp. n., and Rhagovelia santanderi sp. n., from the Upper and Middle Magdalena River Valley respectively; Rhagovelia carina sp. n., Rhagovelia tricoma sp. n., and Rhagovelia barbacoensis sp. n., from Altaquer, Río Ñambi; Rhagovelia caunapi sp. n. from Río Caunapi; Rhagovelia tumaquensis sp. n., from Tumaco, Río Mejicano; Rhagovelia jagua sp. n., from Eastern Andes; Rhagovelia mocoa sp. n. and Rhagovelia umbria sp. n., from Amazonas region. Rhagovelia tantilla Drake & Harris is recorded from Colombia, for the first time; the description of macropterous morph of Rhagovelia espriella Padilla-Gil, 2011 and a key to the Rhagovelia, angustipes complex of Colombian species are provided.